Hubungan antara Suasana Lingkungan Belajar dengan Minat Belajar Murid di TPQ Masjid Baiturrahman Kelurahan Koto Lalang Kota Padang - Giovando, Andre; Setiawati, Setiawati; Wahid, Syafruddin (Universitas Negeri Padang, 2018)
This research is based on the low learning interest of students at TPQ Masjid Baiturrahman Kelurahan Koto Lalang Kota Padang. This study aims to see the description of the atmosphere of the learning environment, description of interest in learning and see the relationship between the atmosphere of learning environment with learning interest of students at TPQ Masjid Baiturrahman. This research is a quantitative research with correlational type. The population in this study is 43 people. Samples were taken as many as 32 people using stratified random sampling technique. Data collection techniques are questionnaires, and data collection tools are the percentages for viewing the description. And to see the relationship using product moment formula. The results showed: (1) the atmosphere of student learning environment is less conducive; (2) student interest is classified as low; and (3) there is a significant relationship between the atmosphere of the learning environment with student learning interest. Suggested to: TPQ management is expected to improve the physical condition of mosque building so that the learning process at TPQ become conducive, and to the teacher expected to create a conducive learning environment atmosphere, and the teacher is expected to make the students feel close to the teacher.